When to apply propess to provide the best activity: In the morning or evening? - Büyük, Gül Nihal; Sarıaslan, Seval; Kansu Çelik, Hatice; Uzunlar, Özlem (Journal of Surgery and Medicine, 2019)
Aim: Propess is a drug of choice in our daily practice for induction of labor. The dosing plan of the drugs can be idealized by arranging them according to the chronobiological model. The aim of this study is to investigate the “time of administration” suggestions on chronotherapy for propess. Methods: Our study was conducted retrospectively by examining the records of pregnant women who were given propess at Zekai Tahir Burak Women's Health Training and Research Hospital between 2008-2018. A total of 2694 patients were included in the study. Two groups were allocated according to the time of drug administration. The time from application to birth was calculated. Results: Logistic regression analysis were performed for risk factors and we found that the time of drug administration was effective on duration to labor. The time from drug administration to labor was 18.0±4.0 hours in the morning group and 19.1±3.9 hours in the evening group (p<0.001) Conclusion: It appears; drugs used for labor induction in the morning may increase drug efficacy and bioavailability. At this point birth becomes compatible with body biorhythm and the time to labor can be shortened.